Fake it till you bake it - Wesley, Jamie (St. Martin's Griffin, 2022)
"A reality star and a cupcake-baking football player pretend to be a couple in order to save his bakery in this sweet and sexy romance from Jamie Wesley, Fake It Till You Bake It. Jada Townsend-Matthews is the most reviled woman in America after turning down a proposal on a reality dating show. When she comes home to lick her wounds, Jada finds herself working at San Diego's newest cupcake bakery, Sugar Blitz, alongside the uptight owner and professional football player Donovan Dell. When a reporter mistakenly believes Jada and Donovan are an item, they realize they can use the misunderstanding to their advantage to help the bakery and rehabilitate Jada's image. Faking a relationship should be simple, but sometimes love is the most unexpected ingredient. Fake it Till You Bake It is a sweet confection of a novel, the perfect story to curl up with and enjoy with a cupcake on the side"--